Development of engine control system using real time simulator - Kimura, A.; Maeda, I. (1996 IEEE International Symposium on Computer-Aided Control System Design, 1996)
In automotive manufacturing, the use of precise control is increasing to satisfy customers' needs, such as fuel economy and air quality. To provide sufficient utility to customers, engine control systems are becoming complicated. We applied two types of real time simulators to the development of an engine control system. One is the engine and vehicle simulator which receives the actuator signals, calculates the engine operating conditions such as the engine output torque, air fuel ratio, engine speed and vehicle behavior, vehicle speed reaction force and outputs sensor signals. The other is the control logic simulator substituting for a part of the engine control logic on CPUs. An application of fuel injection control system was conducted and the simulators have the potential to efficiently improve the development process of engine control systems.